The Chemical Profile of Senna velutina Leaves and Their Antioxidant and Cytotoxic Effects - Campos, Jaqueline Ferreira (2018)
Natural products can be a source of biomolecules with antioxidant activity which are able to prevent oxidative stress-induced diseases and show antitumor activity, making them important sources of new anticancer drug prototypes. In this context, this study aimed to analyze the chemical composition of an ethanol extract of Senna velutina leaves and to assess its antioxidant and cytotoxic activities in leukemic cells. The antioxidant properties were evaluated using a DPPH free radical scavenging assay and by examining the extract's inhibition of AAPH-induced lipid peroxidation in human erythrocytes. Its cytotoxicity and possible mechanisms of action were assessed in Jurkat and K562 leukemic cell lines. The ethanol extract contained flavonoids, such as epigallocatechin, epicatechin, kaempferol heteroside, rutin, and dimeric and trimeric proanthocyanidin derivatives. The extract exhibited antioxidant activity by scavenging free radicals and antihemolytic action, and it decreased malondialdehyde content in human erythrocytes. Furthermore, the extract also induced leukemic cell death by activating intracellular calcium and caspase-3, decreasing mitochondrial membrane potential, and arresting the cell cycle in S and G2 phases. Hence, S. velutina leaf extract contains antioxidant and antileukemic biomolecules with potential applications in diseases associated with oxidative stress and in the inhibition of tumor cell proliferation.